FATE OF SEAGRASS PRODUCTION AS ASSESSED BY CAGE EXPERIMENTS IN Enhalus Acoroides BED IN GILIMANUK BAY, BALI, INDONESIA - Azkab, M. Husni (Marine Research in Indonesia, 2008)
In 2006, the amounts of seagrass products floating away and depositing were measured by in situ cage experiments in a monospecific seagrass meadow of Enhalus acoroides in Gilimanuk Bay, Bali Island. Results showed that the average rates of the floating and depositing leaves were 4.03 + 0.28 and 7.95 + 0.31 gram dry weight shoot-1 day-1 respectively. To express it in another way, about 66.4 % of seagrass production was deposited on the seagrass bed and 33.6 % floated away from the seagrass bed.